Lipid Profile in Type 2 Diabetes Mellitus Patients With and Without Diabetic Retinopathy - Fadhlan Hatta Agustian; Yulia Wardany (Talenta Publisher, 2024)
Background: Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia due to abnormalities in insulin secretion, insulin action, or both. Objective: To analyze differences in the proportion of lipid profile categories in type 2 DM patients with and without diabetic retinopathy. Methods: This was a hospital-based cross-sectional study with 45 samples. The independent variables assessed were the lipid profile, including LDL, HDL, triglycerides, and total cholesterol levels. The dependent variable assessed was the incidence of diabetic retinopathy. The analysis used were univariate and bivariate (Chi-square and Fisher exact). Results: The prevalence of diabetic retinopathy was 37.8%, consist of 17.8% of NPDR and 20% of PDR. There were significant differences in the proportion of LDL categories (p=0.007) and total cholesterol (p=0.038) in type 2 DM patients with and without diabetic retinopathy, and there were no significant differences in the proportion of HDL categories (p=0.719) and triglycerides (p=1) in type 2 DM patients with and without diabetic retinopathy. Conclusion: There were significant differences in the proportion of LDL categories and total cholesterol in type 2 DM patients with and without diabetic retinopathy.